Hesperozygis ringens (Benth). Epling: caracterização química e atividade biológica - Dolwitsch, Carolina Bolssoni (2020)
Hesperozygis ringens (Benth.) Epling (Lamiaceae), is an aromatic plant, endemic to southern Brazil, it is popularly used as an insecticide, but it is not properly studied in the literature. In view of this gap, the objective of this work was to evaluate the antioxidant, antimicrobial, cytotoxic, genotoxic, trypanocidal and nematicide activity of Hesperozygis ringens extracts obtained by supercritical fluid extraction using carbon dioxide (SFE-CO2) and ultrasoundassisted extractions with ethanol (UAE-EtOH) in addition to obtaining an overview of the chemical composition of the species. In the SFE-CO2 extract were found major compounds: pulegone, limonene, linalool, ρ-mentone, neo-menthol, transcariophylene and β-Sitosterol. In the UAE-EtOH extract, rosmarinic acid, chlorogenic acid, caffeic acid, ferulic acid, rutin, ρ- cumaric acid, vanylic acid, resveratrol, luteolin, quercetin, apigenin and canferol were detected. Both extracts showed antioxidant activity against the DPPH radical (IC50 172,38 μg mL−1 and 9516 μg mL−1) for UAE-EtOH and SFE-CO2 extracts, respectively.). The UAEEtOH extract did not show antimicrobial activity against the tested microrganisms. The SFECO2 extract showed an inhibition halo in the diffusion disk assay against the Pseudomoas aeruginosa bacteria and the fungus Candidaa albincans, with lowest inhibiting concentration of 1.46 mg mL−1 in the microdilution assay. Well diffusion assay, demonstrated that SFECO2 extract in 10 mg mL−1 inhibited the bacteria Sthaphylococcus aureus ATCC33591, Sthaphylococcus aureus ATCC29213 and Sthaphylococcus epidermidis ATCC35984. Neither extract presented cytotoxicity or genotoxicity against human mononuclear blood cells at the concentrations 625-10000 μg mL-1 and 31.25-250 μg mL‾1, for SFE-CO2 and UAEEtOH respectively. Both extracts eliminated 100% of Trypanosoma evansi at the end of the time evaluated in the experiment (9h) in concentrations 2500 μg mL‾1, 1250 μg mL‾1, 625 μg mL‾1 (SFE-CO2) and 250 μg mL‾1, 62.5 μg mL‾1, 31.25 μg mL‾1 (UAE-EtOH). The SFE-CO2 extract at 10 mg mL‾1and the UAE-EtOH extract in 80 mg mL‾1and in their dilutions eliminated 80% of Meloidogyne javanica J2 larvae. Thus, the extractions proved to be adequate for the chemical composition analysis of H. ringens, which showed antioxidant, antimicrobial, trypanocidal, nematicide activity without showing cytotoxicity and genotoxicity. Therefore, of H. ringens can be an alternative for the development of new drugs